Subacute Sclerosing Panencephalitis Resurgence - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Five cases of subacute sclerosing panencephalitis (SSPE) are reported from the California Department of Health Services, Richmond, CA.